(untitled) (Docentes 2.0 Journal, 2020)
The development of thought as formation of cognitive competence in preschool to primary students, in correlation with the formation of an investigative spirit and textual understanding, undoubtedly contribute to the materialization of pedagogical models such as constructivist or sociocritical. This work, therefore, had the objective of generating a correlational instrumentalization of thought, investigative training and textual reading in classroom or research hotbed situations, as a strengthening of curricular development with a view to comprehensive training. In this study, contributions on the development of thought have been vital; the formation of the investigative, observational, experiential spirit; and the development of a textual competence. The assumed hermeneutical qualitative methodology corresponds to the heuristic-significant, text linguistic, semiotic, and investigative mixed method. As results, the instrumentalization in a correlational matrix, with three articulated inventories (thought-research-textual understanding). To obtain results, the methods were applied. Another investigative result is the basic mindset in which the theoretical, methodological, ethical-philosophical, and practical approach of the objects of study has been presented. The instrumentalization in this case was carried out in an integrated, adjuvant way, unlike the cognitive approach as it is done by conceptual pedagogy. This work provides the teacher with a useful tool for the inclusion of learning and activities in or outside the classroom, leading to quality training.